ANALISIS MENGUKUR KINERJA KEUANGAN BERDASARKAN RASIO KEUANGAN PADA PT AIRASIA PERIODE 2021-2023 - Priscilla Austin; Liphing Gunawan; Gavrila, Lukas; Cahyasari, Dyah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study examines the financial performance of PT AirAsia Indonesia Tbk from 2021 to 2023 using a quantitative approach, focusing on liquidity, solvency, activity, and profitability ratios. The research aims to analyze the company’s financial statements to monitor its economic development over time. The findings reveal challenges in liquidity, with ratios such as Current Ratio (CR), Quick Ratio (QR), and Cash Ratio (CAR) consistently below industry standards. Solvency ratios show high debt dependency and negative equity, signaling financial instability. Conversely, activity ratios like Fixed Asset Turnover Ratio (FATR) and Inventory Turnover Ratio (ITR) demonstrate efficient asset utilization, although the Working Capital Turnover Ratio (WCTR) remains negative, indicating inefficiencies. Profitability ratios, including Net Profit Margin (NPM), Return on Investment (ROI), and Return on Equity (ROE), highlight declining trends and suboptimal performance. This research underscores the importance of financial analysis in understanding company performance and provides insights for improving financial management to ensure long-term sustainability and competitiveness. Data were obtained from secondary sources, specifically financial reports from 2021 to 2023, and analyzed systematically to ensure objective and accurate results.